HUBUNGAN KEJADIAN BBLR DENGAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR - Purwanti, Sugi; Suryandari, Artathi Eka (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Asphyxia means progressive hypoxia, accumulation of carbon dioxide and acidosis, if this process goes too far can result in brain damage or death. Asphyxia can also affect other vital organ functions. The factors that influence the occurrence of neonatal asphyxia are maternal disease and preterm (premature) placenta previa, placental abruption and prolonged labor. Objective: To determine the correlation between LBW (low birth weight) incidence and asphyxia incidence. Research Methods: This type of research used an observational analytic method with a case control approach. The population in this study were all newborns at BKMIA KARTINI 1 January - 31 December 2017 as many as 749. The samples used were 150 with cases of 75 samples and controls 75 samples. The analytical method in this study used Chi-square. Research Results: Most babies did not LBW (51%), Most of the infants experienced asphyxia (60.7%). There is a correlation between the incidence of LBW and the incidence of Asphyxia with p value 0.000. Suggestion: Need to provide information about asphyxia both regarding the causal factors and complications and management of asphyxia that can be done by placing posters or leafleat distribution so that pregnant women have information about asphyxia. Keywords:Low Birth Weight, Asphyxia